Pemaknaan Kontekstual Syukur Dan Relevansinya Bagi Pembentukan Karakter Generasi Alpha : (Studi Kontekstual QS. Luqman Ayat 12) - Arlis Karlina; Komarudin Sassi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Generation Alpha, born since 2010, grows up in a rapidly evolving digital environment, requiring a character education approach that aligns with contemporary challenges. This study aims to explore the meaning of gratitude (shukr) in Surah Luqman verse 12 through a thematic (maudhu’i) and contextual interpretation, drawing on the insights of M. Quraish Shihab in Tafsir al-Mishbah. The findings reveal that gratitude is not limited to verbal acknowledgment, but represents active awareness in utilizing blessings responsibly for social good. The values of gratitude include awareness of blessings, recognition of Allah as their source, and constructive application of those blessings. These values significantly contribute to the development of spiritual and social character in Generation Alpha. Theoretically, this study enriches the contextual interpretation of the Qur’an, and practically, it provides a foundation for developing Islamic character education models that are adaptive, integrative, and relevant to the digital era